Length-weight and length-length relationship for three marine fish species of commercial importance from southwestern Atlantic Ocean coast - Biolé, Fernanda Gabriela (2020)
Length-weight (LWR) and length-length (LLR) relationships were described for three marinefish  species  Odontesthes  argentinensis  (Valenciennes,  1835),  Urophycis  brasiliensis  (Kaup,  1858)  andBrevoortia aurea (Spix & Agassiz, 1829) from the southwestern Atlantic Ocean coast, among sampling sites between 36 and 38°S. These species have commercial importance in fisheries. Latitudinal change in LWR could suggest the existence of different subpopulations throughout their distribution ranges. A total of 2,167 specimens were collected between August 2015 and October 2018 using lift nets (mostly 10 mm mesh size) and ﬁshing rods 100-200 m offshore. Both relationships were highly significant (P < 0.0001) for all species and produced robust coefficients of determination (R2 > 0.94). The latitudinal trend of a and b parameters of LWR showed different patterns for each species. This study provides a new maximum length for B. aurea and describes thevariation of the regression parameters. New length-length relationships of these species were reported.